The Digital Era and The Knowledge Revolution: Perspectives From Islamic Epistemology and Islamic Religious Education - Cita Suci; Eva Dewi (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
This article examines the intersection of the digital era's knowledge revolution and the Islamic epistemological framework, and its implications for Islamic Religious Education (PAI). The digital era described by Manuel Castells as the